1998
DOI: 10.1021/la970979a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Long-Term Effects of Electromagnetic Radiation on Solutions and Suspended Colloids

Abstract: The mechanisms of the electromagnetic water treatment have been studied with a multitude of techniques and it has been found that the gas/water interface is essential to perturb water and suspended colloids. Perturbation of the gas/liquid interface results in nonequilibrium conditions which require hours to relax. Certain magnetic and electric fields also produce small amounts of ozone, superoxide, hydrogen peroxide, or atomic hydrogen. The addition of hydrogen peroxide or hydrogen did not produce equivalent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 26 publications
4
53
1
Order By: Relevance
“…Although the precise mechanisms of the EMF effect has not been yet fully elucidated, some theoretical and experimental considerations have suggested that EMF act via a colloid/water interface [6][7][8] . In this regard, Colic and Morse 6 working with oscillating radio-frequencies EMF on colloids in water proposed that the electromagnetic treatment (EMT) effect results from the perturbation of the gas/liquid interface and that outgassing removes all the observed effects which persist for hours and even days (Zeta potential, turbidity, …) 9 . This interface has been shown to play a key role in emulsion stability, cavitation, and biological reactivity 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise mechanisms of the EMF effect has not been yet fully elucidated, some theoretical and experimental considerations have suggested that EMF act via a colloid/water interface [6][7][8] . In this regard, Colic and Morse 6 working with oscillating radio-frequencies EMF on colloids in water proposed that the electromagnetic treatment (EMT) effect results from the perturbation of the gas/liquid interface and that outgassing removes all the observed effects which persist for hours and even days (Zeta potential, turbidity, …) 9 . This interface has been shown to play a key role in emulsion stability, cavitation, and biological reactivity 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The EMF-treated water was analyzed with capacitive discharge measurements (17) and it was concluded that some kind of unspecified changes in water structure occured and lasted for hours. Colic and Morse have recently studied a multitude of phenomena involving EMF effects (18)(19)(20). Colloid chemical and bulk physicochemical techniques were used along with molecular techniques to quantify the EMF water treatment effects.…”
Section: Introductionmentioning
confidence: 99%
“…When working with RF and microwave fields, it was also concluded that preliminary outgassing of water prevented the EMF effects on the behavior of suspensions and solutions. Detailed studies of the gas/liquid interface (18) revealed that it is the primary target of the EMF action and the memory effect. Gas/liquid interfaces seem to relax much more slowly than pure water when perturbed.…”
Section: Introductionmentioning
confidence: 99%
“…It is currently believed that the effects of magnetic water treatment are related to changes in the conformation of water molecules, ions, or adsorbed ions on the solid surface (3,4,11,18). Colic and Morse propose that this is due to modification of the water structure due to breakage of hydrogen bonds (4), arising from a sonoluminescence effect at the water/gas interface.…”
Section: Discussionmentioning
confidence: 99%
“…A number of investigations have been carried out on the effects of magnetic and electromagnetic treatment of aqueous solutions and suspensions (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), colloidal particles (4)(5)(6)(7)(8), and biological organisms, as well as practical industrial processes including prevention of scale deposition on pipes (1,21). The effects arise from exposure to radiofrequency (RF) electromagnetic fields or magnetic fields of low flux density and are manifested for several hours after exposure has terminated.…”
Section: Introductionmentioning
confidence: 99%